Challenges and barriers to conducting commercial beekeeping education programs in Florida - Benge, Matt; Amy Vu (Advancements in agricultural development, 2023)
Honey bees are vital to Florida agriculture as they play an important role in pollinating a variety of the state’s crops, and the demand for honey bee pollination and bee-related products continues to increase as the need for more food increases. Cooperative Extension plays an important role in Florida’s agricultural sector, yet many extension agents do not focus much time and attention on commercial beekeeper education. Using the program development model, we sought to understand the challenges and barriers of Florida agriculture extension agents to conducting commercial beekeeping programs. We conducted a focus group with the Honey Bee Extension Education Team to identify potential barriers and challenges. One major finding is that agriculture extension agents are using a variety of definitions and descriptions when classifying who a commercial beekeeper is. The major challenges that affect Florida Extension agents conducting commercial beekeeping programs are a lack of resources, little technical/subject matter knowledge and experience, lack of trust with commercial beekeepers, understanding clientele needs, and other agent job responsibilities take priority demands. Florida Extension needs to provide a strategic plan with specific goals, objectives, and training for agriculture extension agents to conduct commercial beekeeping programs.